Suitable particle-size biochar enhances resilience of potato production and soil environmental to irregular precipitation in semiarid region - Zhaoyang Li; Nan Shi; Zhimin Yang; Yubo Cao; Shimeng Fan; Musawer Abbas; Weixing Shan; Ansabayeva Assiya; Zhikuan Jia; Enke Liu; Kadambot H.M. Siddique; Ruixia Ding; et al. (Bioresource Technology, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Cationic Dendrimer-Directed Pore Architecture in Polyamide Membranes for Tunable Ion Separation - Bingbing Yuan; Menghan Wu; Jinmiao Cui; Lei Zhang; Zequn Liao; Ping Hu; Yuling Ren; Lihong Liu; Siheng Zhao; Meng You; Dongxiao Yang; Q. Jason Niu (Water Research, 2026)

Antibacterial mechanisms of terpinen-4-ol against Aeromonas hydrophila - Kaiqi Lian; Xiangfeng Meng; Yuhang Wang; Shengming Ma; Xiaolong Li; Ren Ren; Yuling Liu; Lingling Zhou; Renhai Peng (Archives of Microbiology, 2026)

Antioxidant activities of three enzymatic hydrolysates from Stichopus japonicus on HaCaT cells in vitro and zebrafish in vivo - Xue Li; Fanying Meng; Tong Sun; Renfang Zhang; He Sun; Xinting Shao; You-Jin Jeon; Yong Li; Yuling Ding (Natural Product Research, 2026)

Advances on Sporisorium reilianum: microbiology along with chemistry, bioactivity, and application - Yihua Wang; Yansong Meng; Zezhuang Hao; Haohan Yang; Zhixin Shen; Denghui Yu; Ye Wang; Shuguang Guan; Yuling Ding; Yong Li (Folia Microbiologica, 2026)

Deep fertilization effects on potato production and GHG emissions depend on soil C:N:P-enzyme interactions: Evidence from a 4-year study - Zhaoyang Li; Nan Shi; Yixuan Yuan; Haiyang Chang; Yuling Meng; Weixing Shan; Moskvicheva Elena; Ansabayeva Assiya; Zhikuan Jia; Xiaolong Ren; Kadambot H.M. Siddique; Ruixia Ding; et al. (European Journal of Agronomy, 2026)

Adjusting fertilization depth for sustainable potato production in arid and semi-arid regions - Zhaoyang Li; Yukang Wang; Nan Shi; Yixuan Yuan; Lianjun Wei; Weixing Shan; Medelbek Meruyert; Ansabayeva Assiya; Zhikuan Jia; Kadambot H.M. Siddique; Ruixia Ding; Peng Wu; et al. (Field Crops Research, 2026)

Epicoccum sorghinum as a leaf spot disease-causing pathogen in Lithocarpus litseifolius in China - Yuling Wang; Meng Li; Changjiang Liu; Guolin Cai; Mengxing Wang; Wuping Yan; Jianfeng Chen (Crop Protection, 2026)

Biochar and moisture variability shape soil carbon pools via microbial carbon-degrading genes - Yue Pan; Tingting Tan; Jie Meng; Hongpeng Guo; Yingbo Dong; Yukui Cui; Na Yu; Xinxin Jin; Yuling Zhang; Hongtao Zou; Nanthi Bolan; Kadambot H.M. Siddique (Journal of Environmental Management, 2026)

An epoxy-based composite coating with CoFeNi/N-doped carbon for integrated flame retardancy, photothermal conversion, and microwave absorption in thermal management - Biyu Huang; Yuling Wang; Yusheng Tong; Jie Shen; Haopeng Zhang; Lei Liu; Meng Liu; Shaoxiang Li; Chuanmei Jiao; Xilei Chen (Chemical Engineering Journal, 2026)

The Role of HIF-1α/BNIP3 Pathway in Hippocampal Neuronal Autophagy in Epilepsy - Huimin Kuang; Youshi Meng; Xinran Qin; Kai Qian; Chi Gong; Sijun Li; Lin Zhang; Xiaohang Gan; Yuling Lu; Yuan Wu (Molecular Neurobiology, 2026)

High-throughput discrimination of chlorogenic acid isomers in Lonicerae Japonicae Flos by U-shaped mobility analyzer-mass spectrometer - Meng Ding; Luwei Zheng; Ao Zhou; Yuling Li; Yiming Wang; Xiaoqiang Zhang; Wenjian Sun; Wen Gao; Ping Li; Hua Yang (Food Chemistry, 2025)

Sulfate-mediated enhancement of simultaneous nitrate and hexavalent chromium removal in Fe(0)-based autotrophic bioprocesses - Meng Ren; Chuanjin Xia; Yidan Zhang; Wanying Jia; Mengjiao He; Linfeng Xu; Yuling Zhu (Journal of Environmental Chemical Engineering, 2025)

Enhancement of the simultaneous bio-reduction of chromium(VI) and nitrate with a novel solid electron donor: Soluble organics-Fe3O4-Hydrochar prepared with rice husk and Fe(III) ions - Meng Ren; Yidan Zhang; Chuanjin Xia; Weidong Cheng; Yuling Zhu (Chemical Engineering Journal, 2025)

Botany, chemistry, bio-activity, and application of Polygonatum odoratum (Mill.) Druce: a comprehensive review - Yiwen Zhang; Xueyan Li; Denghui Yu; Zhaoyi Yang; Zhixin Shen; Yansong Meng; Yuling Ding; Yong Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Target-activated DNAzyme and ion-functionalized DNA nanospheres enable dual cfDNA homogeneous electrochemical analysis for tuberculosis diagnosis - Yanming Meng; Runlian Qu; Yue Wang; Chunying Zhang; Wu Peng; Yuling Xiao; Hongxia Ruan; Hao Chen; Binwu Ying; Piaopiao Chen (Chemical Engineering Journal, 2025)

Autotrophic Uranium (VI) bioreduction in groundwater by siderite: Comparison with sulfur and zero-valent iron - Yidan Zhang; Meng Ren; Chuanjin Xia; Wenzhong Wang; Yuling Zhu (Environmental Research, 2025)

Peptides from Dalian Stichopus japonicus: Antioxidant Activity and Melanogenesis Inhibition In Vitro Cell Models and In Vivo Zebrafish Models Guided by Molecular Docking Screening - Xue Li; Fanying Meng; Tong Sun; Zezhuang Hao; Yihua Wang; Yunfei Jiang; Ye Wang; Yong Li; Yuling Ding (Marine Biotechnology, 2025)

Encapsulation of oleanolic acid into cyclodextrin metal-organic frameworks by co-crystallization: Preparation, structure characterization and its effect on a zebrafish larva NAFLD model - Meng Li; Dongxia Hu; Dian Zhang; Guangya Xu; Di Wu; Chengcheng Gao; Linghan Meng; Xiao Feng; Weiwei Cheng; Zhenjiong Wang; Yuling Yang; Xiaozhi Tang (Food Research International, 2025)

Chromium(VI) and nitrate removal from groundwater using biochar-assisted zero valent iron autotrophic bioreduction: Enhancing electron transfer efficiency and reducing EPS accumulation - Chuanjin Xia; Weidong Cheng; Meng Ren; Yuling Zhu (Environmental Pollution, 2025)

Hyperbranched polymer wrapped UIO-66-NH2 as covalent intermediate layer to enhance polyamide membrane for Li+/Mg2+ separation and acid/alkaline stability - Bingbing Yuan; Shuang Yuan; Chaozheng Jia; Ping Hu; Siheng Zhao; Yuling Ren; Meng You; Shengchao Zhao; Kuo Chen; Xiaozhuan Zhang; Dongxiao Yang; Juhui Jiang; et al. (Desalination, 2025)

First wetland mapping at 10-m spatial resolution in South America using multi-source and multi-feature remote sensing data - Weiwei Sun; Gang Yang; Yuling Huang; Dehua Mao; Ke Huang; Lin Zhu; Xiangchao Meng; Tian Feng; Chao Chen; Yong Ge (Science China Earth Sciences, 2024)

Study on the chemical composition and anti-fungi activities of anthraquinones and its glycosides from Rumex japonicus Houtt. - He Sun; Dandan Xiao; Xue Li; Tong Sun; Fanying Meng; Xinting Shao; Yuling Ding; Yong Li (Journal of Natural Medicines, 2024)

New Butterfly-Shaped Naphthalimide-Based AIE Gens: Synthesis and Photophysical Properties - Hui Zhang; Meng Zhou; Yuling Zhao; Tianzhi Yu; Xvyan Xv (Journal of Fluorescence, 2024)

Mycorrhizal associations relate to stable convergence in plant–microbial competition for nitrogen absorption under high nitrogen conditions - Zhenggang Du; Lingyan Zhou; Madhav P. Thakur; Guiyao Zhou; Yuling Fu; Nan Li; Ruiqiang Liu; Yanghui He; Hongyang Chen; Jie Li; Huimin Zhou; Ming Li; et al. (Global Change Biology, 2024)
Nitrogen (N) immobilization (Nim, including microbial N assimilation) and plant N uptake (PNU) are the two most important pathways of N retention in soils. The ratio of Nim to PNU (hereafter Nim:PNU ratio) generally reflects the degree of N limitation for plant growth in terrestrial ecosystems. However, the key factors driving the pattern of Nim:PNU ratio across global ecosystems remain unclear. Here, using a global data set of 1018 observations from 184 studies, we examined the relative importance of mycorrhizal associations, climate, plant, and soil properties on the Nim:PNU ratio across terrestrial ecosystems. Our results show that mycorrhizal fungi type (arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi) in combination with soil inorganic N mainly explain the global variation in the Nim:PNU ratio in terrestrial ecosystems. In AM fungi‐associated ecosystems, the relationship between Nim and PNU displays a weaker negative correlation ( r = −.06, p r = .25, p

Relationship between carbon pool changes and environmental changes in arid and semi-arid steppe—A two decades study in Inner Mongolia, China - Hang Li; Banghui Yang; Yu Meng; Kai Liu; Shudong Wang; Dacheng Wang; Hongyan Zhang; Yuling Huang; Xingtao Liu; Dehui Li; Long Li; Xueke Li (Science of The Total Environment, 2023)

Construction of starch-sodium alginate interpenetrating polymer network and its effects on structure, cooking quality and in vitro starch digestibility of extruded whole buckwheat noodles - Xiang Xu; Linghan Meng; Chengcheng Gao; Weiwei Cheng; Yuling Yang; Xinchun Shen; Xiaozhi Tang (Food Hydrocolloids, 2023)

A method for evaluating drug penetration and absorption through isolated buccal mucosa with highly accuracy and reproducibility - Shuangqing Wang; Lei Liu; Saige Meng; Yuling Wang; Daofeng Liu; Zhonggao Gao; Along Zuo; Jianpeng Guo (Drug Delivery and Translational Research, 2022)

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Construction of chlorogenic acid-containing liposomes with prolonged antitumor immunity based on T cell regulation - Yun Zhang; Yanfang Yang; Jun Ye; Yue Gao; Hengfeng Liao; Junzhuo Zhou; Yu Feng; Dongdong Liu; Yingying Meng; Xiaoguang Chen; Lili Gao; Yuling Liu (Science China Life Sciences, 2021)

The contribution of oxygen-containing functional groups to the gas-phase adsorption of volatile organic compounds with different polarities onto lignin-derived activated carbon fibers - Fanyue Meng; Min Song; Yuexing Wei; Yuling Wang (Environmental Science and Pollution Research, 2019)

Calcium regulates glutamate dehydrogenase and poly-γ-glutamic acid synthesis in Bacillus natto - Yonghong Meng; Guiru Dong; Chen Zhang; Yuanyuan Ren; Yuling Qu; Weifeng Chen (Biotechnology Letters, 2016)

Erythropoietin Mediates Neurobehavioral Recovery and Neurovascular Remodeling Following Traumatic Brain Injury in Rats by Increasing Expression of Vascular Endothelial Growth Factor - Ye Xiong; Yanlu Zhang; Asim Mahmood; Yuling Meng; Changsheng Qu; Michael Chopp (Translational Stroke Research, 2011)